How Psychoanalytic Process’s Work: Considering the Relation between Traditional Theory and Contemporary Scientific Theory and Techniques - Sinal, Aysin (Mediterranean Journal of Social Sciences, 2020)
The main aim of this article is to try and demonstrate the difficulties and obstacles involved during the process of psychoanalytical therapy, mainly a case conceptualization by taking both traditional Psychoanalytical theory and contemporary scientific findings into consideration. By looking at the traditional theory of psychoanalysis, it is palpable that interpretation and the study of the human mind will eventually deem the issue of subjectivity undeniable, as you will see from the reference section, of those used; essential materials from the International Journal of psychoanalysis, introductory lectures of Freud, and studies of hysteria and also for the contemporary reference, lecture notes of Wilma Bucci (2009). This article will focus mainly on resistance, and what then is the cure? Freud described the notion of an analytic cure in ‘Introductory Lectures on Psycho-Analysis’. Through this method, psychoanalysis sets itself up as the ‘talking cure’ and communication, its weapon. Any process of communication which does not have the aim of providing a cure isn’t in the strict sense of the word, psychoanalysis. According to Freud, the ego is the source for three types of resistance while the super-ego and the Id is responsible for each other. This article has no methodology since all the information used is based on theoretical information obtained from reliable sources and all references have been included accordingly. According to Wilma, the contemporary psychoanalytic process differs. Due to the nature of this article, the conclusion is the fact that further research is required to observe how exactly theory relates to technique and therapy becomes more effective.